2013
DOI: 10.1093/dnares/dst044
|View full text |Cite
|
Sign up to set email alerts
|

Diet Alters Both the Structure and Taxonomy of the Ovine Gut Microbial Ecosystem

Abstract: We surveyed the ruminal metagenomes of 16 sheep under two different diets using Illumina pair-end DNA sequencing of raw microbial DNA extracted from rumen samples. The resulting sequence data were bioinformatically mapped to known prokaryotic 16S rDNA sequences to identify the taxa present in the samples and then analysed for the presence of potentially new taxa. Strikingly, the majority of the microbial individuals found did not map to known taxa from 16S sequence databases. We used a novel statistical modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 40 publications
2
40
0
1
Order By: Relevance
“…While differences in phylum abundances between the two groups were not statistically significant, qualitative differences were observed at the OTU level. Dietary resources have been shown to exert a strong influence on microbial community compositions of both terrestrial and marine mammals (5,47,48). Recent studies observing the influence of diet on gut microbiota of fish and mammalian livestock species have shown that animals that forage manifest greater microbial diversity than those fed from artificial or concentrate sources (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While differences in phylum abundances between the two groups were not statistically significant, qualitative differences were observed at the OTU level. Dietary resources have been shown to exert a strong influence on microbial community compositions of both terrestrial and marine mammals (5,47,48). Recent studies observing the influence of diet on gut microbiota of fish and mammalian livestock species have shown that animals that forage manifest greater microbial diversity than those fed from artificial or concentrate sources (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary resources have been shown to exert a strong influence on microbial community compositions of both terrestrial and marine mammals (5,47,48). Recent studies observing the influence of diet on gut microbiota of fish and mammalian livestock species have shown that animals that forage manifest greater microbial diversity than those fed from artificial or concentrate sources (47)(48)(49). The varied diet of wild Australian sea lions includes a number of species with chitinous body parts, including small crustaceans, rock lobster, and cephalopods such as cuttlefish, octopus, and squid (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Our final database contained 27 290 sequences. In our previous work ( 37 ), we also used the EMIRGE package ( 38 ) to identify novel 16S rDNA genes in the samples. However, using EMIRGE or attempting to assemble the sequence reads, while it might uncover further taxonomic diversity in the samples, will also bias the counting of microbial individuals in complex ways that would undermine the comparisons we planned.…”
Section: Methodsmentioning
confidence: 99%
“…A range of approaches such as increasing feed quality, increasing the ratio of concentrate to forage feed, using rumen modifiers such as defaunation or methanogenesis inhibitors (e.g., mevastatin), using production-enhancing agents such as ionophores and using lipids or fatty acids as dietary supplements have been investigated as a means of manipulating the rumen microbiome to achieve specific outcomes ( Boadi et al, 2004 ; Knapp et al, 2014 ; Caro et al, 2016 ). Although these strategies have yielded varying levels of success, diet has been repeatedly shown to strongly influence rumen microbial structure ( de Menezes et al, 2011 ; Ellison et al, 2014 ; Cobellis et al, 2016 ). For example, Petri et al (2013) reported significant differences in rumen bacterial community structure in mature cattle fed a forage diet versus those on a high concentrate diet while Kocherginskaya et al (2001) described differences in bacterial community composition in cattle fed hay diets compared to those fed corn diets.…”
Section: Introductionmentioning
confidence: 99%